Mind map: interrogative words in Mandarin / Ngien Ming Ming … [et al.] - Ming Ming, Ngien; Sheau Ping, Wee; Richard Thing, Cindy; Nik Fauzi, Sheela Faizura; Chin Ying, Liew (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
"Mind Map: Interrogative Words in Mandarin" explores the integration of mind maps, based on Tony Buzan's theory, into Mandarin interrogative word learning. In a globalized society where language acquisition is crucial, innovative tools like mind maps offer a non-linear and intuitive approach to organizing information. The study addresses the challenge of learners struggling with learning Mandarin interrogative words, proposing a solution through the creative and systematic use of mind maps. By focusing on vocabulary retention, conceptual understanding, system building, and reading comprehension, the study aims to enhance learners' application abilities in both real-life scenarios and exams. "Mind Map: Interrogative Words in Mandarin" combines visual elements with textual information, offering an inventive and graphical method for learners to understand, classify, and utilize interrogative words effectively. The expected outcomes include improved contextual awareness and self-learning skills, making the process of learning interrogative words engaging, effective, and creative. Ultimately, the use of mind maps as a learning tool for interrogative words helps enhance learners' understanding and mastery capabilities.